PENGEMBANGAN SISTEM INFORMASI KEARSIAPAN DOKUMEN TUGAS AKHIR MAHASISWA FAKULTAS PSIKOLOGI UNIVERSITAS NEGERI MAKASSAR - Firmansyah S; Riana T. Mangesa; Sanatang (Program Studi S2 Pendidikan Teknologi dan Kejuruan, 2024)
This research is a type of development research which aims to: (1) produce an archival information system for students' final assignment documents at the Psychology Faculty, Makassar State University; (2) testing the archival information system for students' final assignment documents at the Faculty of Psychology, Makassar State University based on ISO/IEC 25010; (3) see the effectiveness of the archival information system for students' final assignment documents at the Faculty of Psychology, Makassar State University; (4) analyzing the responses of archival information system users to the final assignment documents of Psychology Faculty students at Makassar State University. This research uses the research and development (RnD) method and the waterfall development. The data collection technique used was a questionnaire and documentation, then the data was processed using descriptive statistical analysis techniques. The results of the development prove that the archival information system for students' final assignment documents at the Faculty of Psychology, Makassar State University is suitable for use because it has been declared suitable by a media expert validator. Very effective to use based on effectiveness test questionnaires, very suitable for use based on user responses. And has met the ISO/IEC 25010 testing standards with test results for the functionality suitability aspect of 100% in the